Pengembangan Kriteria Seleksi pada Pisang (Musa sp.) Berdasarkan Analisis Lintas - Desta Wirnas; Sobir Sobir; Memen Surahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
This research was aimed to develop selection criteria based on correlation and path coefficient analysis. The experiment was carried out at CETROFS (Center for Tropical Fruit Studies) field station of Bogor Agricultural University, Tajur. The result showed that plant height, pseudostem diameter, number of leaves, weeks to harvest, finger number per plant, and mean of finger weight were positively correlated with bunch weight. Pseudostem diameter, number of leaves, finger number per plant have strong direct effect on bunch weight, with path coefficient 0.321, 0.264, 0.297, and 0.722, subsequently. However, the plant height showed strong indirect effect on bunch weight through pseudostem diameter. These characters are useful as a selection criteria for developing new variety of banana with higher bunch weight Key words: path coefficient, selection criteria, banana